Novel angiotensin-converting enzyme and pancreatic lipase oligopeptide inhibitors from fermented rice bran - Hu, Jingfei; Wang, Huanyu; Weng, Nanhai; Wei, Tong; Tian, Xueqing; Lu, Jing; Lyu, Mingsheng; Wang, Shujun (Frontiers in Nutrition, 2022)
This study determined the inhibitory activity of oligopeptides against angiotensin-converting enzyme (ACE) and pancreatic lipase through in vitro tests, molecular docking, and enzyme inhibition. The results showed that the IC50 of GLLGY, HWP, and VYGF for ACE inhibition was 1 mg/mL, and the IC50 of HWP for pancreatic lipase was 3.95 mg/mL. Molecular docking revealed that the binding energies between GLLGY, HWP, and VYGF and ACE were −9.0, −8.4, and −9.2 kcal/mol, respectively. The binding free energy between HWP and pancreatic lipase was −7.3 kcal/mol. GLLGY, HWP, and VYGF inhibited ACE compentitively. HWP inhibited pancreatic lipase through non-competition. In vitro simulated gastrointestinal digestion, the three oligopeptides still had inhibitory activity and low toxicity. The results revealed that the peptides GLLGY, HWP, and VYGF may be suitable candidates for further research on ACE inhibition, and HWP may be a suitable candidate for studying pancreatic lipase inhibition.